Peran Relawan Pajak dalam Asistensi Pelaporan SPT Tahunan WPOP di Kota Batam - Arniati, Arniati; Kurniawan, Dedi; Lanniari HS, Rizki; Anjelina, Anjelina; Hasanah, Afriyanti; Darmawan, Arif; Irianto, Danar; Setiyanto, Adi Irawan; Amalia, Diah; Anggraini, Ria; Zelmiyanti, Riri; Utama, Doni Putra; Sabrina, Nova; Rahman, Fuad Arif (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2023)
The Tax Volunteer Program is a concrete step in the dedication of the Batam State Polytechnic academic community to assist the role of the Directorate General of Taxes (DGT) in conducting tax education to increase taxpayer awareness and compliance. This program is also used as PBL which is required for D3 Accounting Study Program students and involves 5 courses in the 4th semester. Volunteers assist in reporting the Individual Annual Tax Return internally at the Batam State Polytechnic and external parties at the Regional Office of DGT Riau Islands as well as several companies cooperating with the Regional Office of DGT Riau Islands. In 2023, tax volunteers succeeded in assisting 808 Individual Taxpayers both from internal Polibatam and outside Polibatam parties. More than 87% of Individual Taxpayers who were assisted by tax volunteers felt the assistance provided by Polibatam Tax Volunteers was very useful and easy for Individual Taxpayers to understand so it could greatly assist Individual Taxpayers in reporting their tax obligations. Many Individual Taxpayers hope that this program can be carried out every year by increasing the skills and understanding of tax volunteers and improving the mechanism for implementing assistance by adding a short tutorial on reporting the Individual Annual Tax Return through e-Filing.